STUDY OF STRENGTH CHARACTERISTICS OF CONCRETE, LOCAL EXPOSURE TO FIRE EXPOSURE - and (Municipal economy of cities. Series: «Economy science», 2013)
The results of testing of concrete and rebar, received higher temperature effects from the fire, made recommendations to strengthen the damaged concrete slab.